(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Asymmetry of abdominal muscles is a potential cause for lowback pain. Most studies assume the rotational strength towards non dominant side to be more but no studies have been conducted to objectively measure the asymmetry. In subjects with spinal deformity like scoliosis which has a rotational component to it, it can be presumed that there could be asymmetry between the oblique force couplehowever this study aims to find out whether this asymmetry exists in normal healthy individuals. By using manual muscle testing for assessing oblique muscle strength only gross asymmetry can be detected. Therefore there is a need for more objective measure to detect subtle discrepancies within strength of both sides. Objective: The objective of this study is to measure the strength of external and internal oblique on both side using handheld dynamometer and to compare the strength on both sides. Methodology:30 healthy young individuals in the age group of 18-30 years were selected to participate in the study. All subjects were right hand dominant.External oblique and internal oblique muscle strength was measured in KGs using a Jamar type of hydraulichand held dynamometer. Results: There was a significant difference between the strength of external obliques on right and left side with strength on right side being more whereas there was no significant difference between strength of internal oblique between right and left side.